The sensitization spectrum to fungal allergens with atopic dermatitis and psoriasis in patients - Alsherees, Hashim; Al-Radhi, Nargis Ali Abdualmeer; Nassar, Fadhal Hassan; Mona, Jammel; Hamza Al-Kraity, Wijdan Rajh (Medical Science Journal for Advance Research, 2023)
The fungal allergy in the progress of atopic dermatitis (AD) and psoriasis (PS) are of special interest and determines the relevance in the study. The aim of the study to conduct a comparative analysis of the sensitization spectrum to fungal allergens in patients with atopic dermatitis and psoriasis. Materials and methods. The study involved patients with AD (Group I, n = 53) and PS (Group II, n=53) and aged group (15-60) years old. Sensitization to fungal allergens was determined by skin prick testing using standardized fungal allergens: Candida albicans, Alternaria alternata, Aspergillus fumigatus, Cladosporium herbarum, Penicillium notatum (ThermoFisher Scientific, Dubai). The concentration of allergen-specific IgE to a mixture of fungal allergens: Penicillium notatum, Cladosporium herbarum, Aspergillus fumigatus, Alternaria alternata (ThermoFisher Scientific, Dubai) were determined by indirect immunofluorescent analysis on a ELISA analyzer. The IgE level test of positive was considered in IgE level ≥ 0.35 kU/l. Results: The highest frequency of sensitization to fungi of the genus Cladosporium herbarum, Aspergillus fumigatus and Alternaria alternata were established In the group of patients with PS. The frequency of sensitization to fungi was higher in the group of patients with PS than in the group of patients with AD. Sensitization to a mixture of fungus allergens, according to the concentration of allergen-specific IgE, it were observed in the group of patients through compared with the group of patients in PS was : 2.7% and AD was 7.5%. Therefore, fungal allergy may play an important role in the etiopathogenesis of AD and PS. The study of the diagnosis and treatment of these pathologies, including a specific allergological examination of patients with AD and PS. To study of the genotyping of fungi causing human infection.